Turkey in the Cold War Ideology and Culture - Örnek, Cangül; Üngör, Çağdaş; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This volume examines the cultural and ideological dimensions of the Cold War in Turkey. Departing from the conventional focus on diplomacy and military, the collection focuses on Cold War's impact on Turkish society and intellectuals. It includes chapters on media and propaganda, literature, sports, as well as foreign aid and assistance.
Keywords: History, Modern; Civilization-History.; World politics; Social history; Europe-History.; Military history; Modern History; Cultural History; Political History; Social History; European History; History of Military